Competition Reduces Response Times in Multiparty Conversation - Holler, Judith; Alday, Phillip M.; Decuyper, Caitlin; Geiger, Mareike; Kendrick, Kobin H.; Meyer, Antje S. (Frontiers in Psychology, 2021)
Natural conversations are characterized by short transition times between turns. This holds in particular for multi-party conversations. The short turn transitions in everyday conversations contrast sharply with the much longer speech onset laten-cies observed in laboratory studies where speakers respond to spoken utterances. There are many factors that facilitate speech production in conversational com-pared to laboratory settings. Here we highlight one of them, the impact of competi-tion for turns. In multi-party conversations, speakers often compete for turns. In quantitative corpus analyses of multi-party conversation, the fastest response de-termines the recorded turn transition time. In contrast, in dyadic conversations such competition for turns is much less likely to arise, and in laboratory experiments with individual participants it does not arise at all. Therefore, all responses tend to be recorded. Thus, competition for turns may reduce the recorded mean turn transition times in multi-party conversations for a simple statistical reason: slow responses are not included in the means. We report two studies illustrating this point. We first report the results of simulations showing how much the response times in a labora-tory experiment would be reduced if, for each trial, instead of recording all respons-es, only the fastest responses of several participants responding independently on the trial were recorded. We then present results from a quantitative corpus analysis comparing turn transition times in dyadic and triadic conversations. There was no significant group size effect in question-response transition times, where the pre-sent speaker often selects the next one, thus reducing competition between speak-ers. But, as predicted, triads showed shorter turn transition times than dyads for the remaining turn transitions, where competition for the floor was more likely to arise. Together, these data show that turn transition times in conversation should be in-terpreted in the context of group size, turn transition type, and social setting.